2013
DOI: 10.1097/igc.0000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer: Sites of Recurrence

Abstract: The peritoneum is the main recurrence site in both early and advanced ovarian cancer. Initial disease spread and extent of surgery are associated with the recurrence risk. This article supports the view that more attention should be directed toward extensive treatment of the peritoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 14 publications
(13 reference statements)
5
43
1
2
Order By: Relevance
“…Ovarian cancer recurrence mainly arises due to chemoresistance, and abnormal regulation of apoptosis is an important mechanism of drug resistance. 2,4 To explore the antiapoptotic role of NR2F6 in ovarian cancer, we generated stable NR2F6 overexpressing cell lines and NR2F6 knockdown cell lines from the A2780 and OVCAR3 ovarian cancer cell lines (Supporting Information Fig. S2A).…”
Section: Nr2f6 Overexpression Confers Cisplatin Resistance To Ovarianmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovarian cancer recurrence mainly arises due to chemoresistance, and abnormal regulation of apoptosis is an important mechanism of drug resistance. 2,4 To explore the antiapoptotic role of NR2F6 in ovarian cancer, we generated stable NR2F6 overexpressing cell lines and NR2F6 knockdown cell lines from the A2780 and OVCAR3 ovarian cancer cell lines (Supporting Information Fig. S2A).…”
Section: Nr2f6 Overexpression Confers Cisplatin Resistance To Ovarianmentioning
confidence: 99%
“…Due to the lack of early diagnosis and the extremely chemoresistant phenotype common to EOC, the 5‐year survival rate for ovarian cancer patients is a dismal 29% . The most effective treatment for EOC is cytoreductive surgery, followed by cisplatin‐based chemotherapy; however, more than 75% of treated patients experience tumor relapse and ultimately die of recurrent disease . The development of resistance to platinum‐based chemotherapy is a serious limitation of long‐lasting, effective treatments for EOC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients with ovarian cancer (approximately 65‐75%) present with advanced‐stage disease (American Joint Committee on Cancer [AJCC] stages III and IV) . Metastatic disease confined to the peritoneal cavity (AJCC stage III) is the most common cause of treatment failure and death in patient with primary and recurrent ovarian cancer . For advanced primary ovarian cancer limited to the peritoneal cavity standard therapy includes maximal cytoreductive surgery (CRS) of macroscopic disease, followed by adjuvant intravenous (IV) chemotherapy (usually carboplatin plus paclitaxel) .…”
Section: Introductionmentioning
confidence: 99%
“…Petrillo et al 6 reported that carcinomatosis as a recurrent disease was observed in 57.3% of patients treated with NAC followed by IDS with no residual tumor after surgery. Amate et al 17 reported that peritoneum is the main site of recurrence (75%) in patients with advanced disease treated by PDS and IDS. In this study, 60.0% of the patients had recurrence in the form of peritoneal dissemination after complete cytoreduction during IDS; these findings are similar to the findings reported by Petrillo et al and Amate et al In addition, in this study, there was no difference in this recurrence pattern compared with the group that had a residual tumor smaller than 1 cm in diameter during IDS (W 2 test).…”
Section: Discussionmentioning
confidence: 99%